Consumption of Fe Tablets as a Risk Factor for Anemia in Adolescents - Syalfina, Agustin Dwi; Mafticha, Elyana; Priyanti, Sari; Irawati, Dian; Maula, Yolanda Sisca (Media Kesehatan Masyarakat, 2023)
Anemia in women of childbearing age, especially adolescent girls, is a nutritional problem that has a long impact on maternal and child health, from pregnancy complications to maternal death and low birth weight babies. Efforts to control and prevent anemia in adolescent girls are carried out through two main activities, including health promotion and the provision of Fe tablets. Fe tablets are consumed by adolescent girls during menstruation and once a week. This study aims to analyze the effect of consuming Fe tablets on anemia in adolescent girls. The type of research used is analytic epidemiological research with cross sectional design. The population is all students at SMPN 1 Trowulan with a sample of 70 students obtained by simple random sampling technique. The data were taken directly at the research site using a questionnaire and a check list instrument and then processed and analyzed using the chi-square test. The results of this study indicate that 80% of respondents do not take Fe tablets during menstruation, 40% do not take Fe tablets once per week, 84.3% are irregular in consuming Fe tablets, there is a significant effect of consuming Fe tablets once per week on anemia. in adolescent girls (p value = 0.017, PR = 3.375, 95% CI = 1.150-9.902). Adolescents who regularly consume Fe tablets once a week will have normal Hb levels. It is expected that health workers will increase socialization about the consumption of Fe tablets during menstruation, distribution of Fe tablets during menstruation